Industrialized building system (IBS) : the problems and strategies to increase the adoption of IBS in Malaysian private sector - Norsyazwani, Masri (2019)
Generally, Industrialized Building System (IBS) has been identified as a potential method on improving the overall construction industry performance. Therefore, Construction Industry Development Board (CIDB) has been actively promoting the use of Industrialized Building System (IBS) in Malaysia Construction Industry 1998. Unfortunately, the used of IBS for building project in Malaysia is still low if compared to CIDB target especially for private sector. In view of this limitation, this study has been carried out to evaluate the effectiveness of current IBS implementation for Malaysian construction industry through the measurement of acceptance level of IBS, determination of the existing problems faced by construction industry and strategies to increase the adoption of IBS. The information and data gathered through questionnaire survey and interview with expert panels and will be analyzing by using average index (AI). The result of this study revealed that about 59% of the respondents have experience using in IBS and also about 79% of them would use IBS in their next project. It means the level of acceptance about IBS higher. Furthermore, lack of knowledge and awareness is the main problem to implement IBS in construction industry. Thus, strategy by training and education is more effective to increase the adoption of IBS in private sector. Not all practitioners can accept it implementation especially company and personnel with less experiences in handling IBS project. It is recommended that the relevant institution which produce young engineer for construction sector must provide a syllabus on IBS which cover technical, and all aspect which needed for effective IBS implementation. This can generate wider range of application of IBS product within the industry.